2019
DOI: 10.1186/s12859-019-2945-8
|View full text |Cite
|
Sign up to set email alerts
|

Helitron distribution in Brassicaceae and whole Genome Helitron density as a character for distinguishing plant species

Abstract: Background Helitron is a rolling-circle DNA transposon; it plays an important role in plant evolution. However, Helitron distribution and contribution to evolution at the family level have not been previously investigated. Results We developed the software easy-to-annotate Helitron (EAHelitron), a Unix-like command line, and used it to identify Helitrons in a wide range of 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 63 publications
2
42
1
Order By: Relevance
“…In maize, Helitrons have significantly influenced genome evolution, leading to genome variation among lines [73] and to a notable diversification of transcripts via exon shuffling of thousands of genes [74]. To refine the annotation of Pacific oyster Helitrons , a structure-based search [75] was performed in addition to the homology based approach described above. The localization of these elements was heterogeneous across the Pacific oyster chromosomes, with LG5 and LG8 showing a higher density of elements (>1SD above the average across chromosomes) (Figure S9).…”
Section: Introductionmentioning
confidence: 99%
“…In maize, Helitrons have significantly influenced genome evolution, leading to genome variation among lines [73] and to a notable diversification of transcripts via exon shuffling of thousands of genes [74]. To refine the annotation of Pacific oyster Helitrons , a structure-based search [75] was performed in addition to the homology based approach described above. The localization of these elements was heterogeneous across the Pacific oyster chromosomes, with LG5 and LG8 showing a higher density of elements (>1SD above the average across chromosomes) (Figure S9).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with A. alpina , A. lyrata , and A. thaliana , LTR‐RT density increases in pericentromeric regions of each chromosome, TIR density decreases in pericentromeric regions, and Helitron density is stable along chromosomes. Abundance of LTR‐RT Copia and Gypsy elements is similar to that of A. alpina (Choudhury et al., 2017), whereas TIR‐CACTA elements and Helitrons seem to be particularly abundant in D. nivalis (Hu et al., 2019). Nucleotide divergence among LTR‐RTs identifies several Copia and Gypsy LTR‐RTs showing recent transposition bursts across the genome of D. nivalis .…”
Section: Resultsmentioning
confidence: 89%
“…et al, Yoshida et al, 2018;David et al, 2019) and are thought to be an unintended consequence of the T-DNA integration process (Tax and Vernon, 2001;Castle et al, 1993;Negruk et al, 1996;Nacry et al, 1998;Laufs et al, 1999). Previously a whole genome sequence was performed for SALK_015201 (Hu et al, 2019). Remapping and variant call analysis of these genomic sequences identified a single base pair deletion of a T nucleotide in the PHYTOCHROME B gene (AT2G18790) at position Chr2:8144002, which corresponds to position 3,370 in the PHYB cDNA ( Figure 4A; Supplemental Figure 7).…”
Section: R a F Tmentioning
confidence: 99%
“…A long hypocotyl phenotype in SALK_015201 lines had been previously reported (Petrov et al, 2013) but a second T-DNA allele in IRR had a wild-type phenotype, prompting us to reconsider the genetic lesion responsible for the long hypocotyl phenotype. Analysis of whole genome sequence data available for this SALK line (Hu et al, 2019) identified a single base pair deletion within the coding sequence of PHYB. Transcriptomic comparison of SALK_015201 and wild type seedlings with and without auxin determined that genes associated with the BAP regulatory module (Bouré et al, 2019) were altered in this T-DNA background.…”
Section: Introductionmentioning
confidence: 99%